Origin of Galactic Cosmic Rays - Herndon, J. Marvin (European Journal of Applied Sciences, 2026)
Galaxies are prominent features as deep into the universe as astronomers can observe. Among the vast number of galaxies, there are only a few prominent morphologies, suggesting a commonality of formative conditions. Galaxies and the origin of elements heavier than hydrogen and helium are inexplicable within the current foundations of astrophysics which are based upon stellar ignition by gravitational collapse, galaxy formation from luminous stars, and abrogation of scientific standards. I have presented evidence for a fundamentally different understanding that began with the realization that thermonuclear reactions in stars, as in hydrogen bombs/devices, are ignited by nuclear fission chain reactions, and ultimately that dark stars in dark galaxies are ignited by nuclear matter jetted out from the galactic center. The luminous stars of galaxies are evidence of the paths of galactic jets that contacted and seeded dark stars with fissionable elements that ignited their thermonuclear fusion reactions. The nuclear matter of the galactic jets, I posited, is the principal origin and source of elements heavier than hydrogen and helium. The spherical assemblage of un-ignited dark stars maintains the dynamical stability of the pattern of luminous stars as required by the velocity dispersions and rotation curves evidenced by Vera C. Rubin. Observation of actinide elements in galactic cosmic rays connects their origin to galactic jets, whose nuclear matter forms actinide elements that sustain nuclear fission chain reactions which ignite thermonuclear fusion reactions thereby making galactic dark stars luminous. Presumably, the nuclear matter jetted from galactic centers is sufficiently energetic to account for the energy distributions observed in galactic cosmic rays. Cosmic rays can now be considered as samples from galactic jets. Theoretical investigations (not models) of nuclear matter condensation of elements from jetted galactic nuclear matter can be validated by comparison with solar/meteoritic abundance patterns, especially the odd atomic mass nuclides.